Creativity Barrier and The Impact on Innovation and Business Performance of SMEs - Rahman, Sarli; Setyawan, Onny; Aprila, Bord Nandre (Jurnal Aplikasi Manajemen, 2024)
Although innovation is recognized as important for a company, not all companies can do it due to some limitations or barriers they have, especially for small and medium-sized companies. One of these barriers is in terms of creativity. This study discussed this issue by investigating how the effect of creativity barriers of SMEs in generating varied, unique, and original ideas on the company's ability to carry out innovative practices, as well as its impact on the business performance of SMEs. Thus, this study aimed to test empirically on 350 SMEs in Riau Province whether barriers to creativity (creativity barriers) can be antecedents of innovation and business performance in the context of cross-sector small and medium-sized enterprises with structural equation modeling (SEM) analysis technique. The findings of this study indicate a significant effect related to the effect of creativity barriers on SMEs' product and process innovation. The results of this study also found that creativity barriers did not have a significant effect on performance. This study's last findings prove the mediation role of the innovation process in the relationship between creativity barriers and performance. The results of this study prove that success in making product innovation can be a differentiating factor that causes some SMEs to grow and develop while others do not, even though they have almost the same limitations or barriers. In practical terms, the results of this study show how important it is for SMEs to always adopt innovative practices, such as making changes, updates, and improvements to improve their business performance.